Psychometric properties of the WHOQOL-SRPB BREF, Brazilian Portuguese version - Zimpel,Rogério R. (2019)
Objective: To test the reliability and the discriminant and convergent validity of the abbreviated Brazilian Portuguese World Health Organization’s Quality of Life Instrument – Spirituality, Religion, and Personal Beliefs module (WHOQOL-SRPB BREF). Methods: In a sample of 404 individuals, we applied a general questionnaire, the WHOQOL-BREF, the long-form SRPB, the Brief Religious-Spiritual Coping Scale (RCOPE), and the Beck Depression Inventory (BDI). Priority was given to the 9-item SRPB assessment: its unidimensionality was tested through confirmatory factor analysis and Rasch analysis. Results: Confirmatory factor analysis of the 9-item SRPB assessment indicated an adjusted model with acceptable fit to data. In the Rasch analysis, general fit measures showed adequate performance. The 9-item SRPB assessment showed good internal consistency (alpha = 0.85), and could differentiate (discriminant validity) between religious and atheist/agnostic respondents (mean = 74.7±14.1 and 56.8±15.5, respectively; t = 6.37; degrees of freedom [df] = 402; p < 0.01) and between non-depressed and depressed respondents (mean = 76.5±12.9 and 67.1±16.5; t = 5.57; df = 190.5; p < 0.01). Correlations (convergent validity) were significant with the positive-RCOPE subscale (r = 0.58, p < 0.01) and the WHOQOL-BREF domains (Pearson coefficient ranging between 0.24 and 0.49; p < 0.01), but were in the negative direction with the negative-RCOPE subscale (r = -0.10, p < 0.05). Correlation with the long-form SRPB domain (r = 0.934) was almost perfect. Conclusion: The Brazilian Portuguese 9-item SRPB has good psychometric properties and confirmed the findings of the long-form Brazilian Portuguese version and the abbreviated English version.